Influence of Supply Chain towards Work Motivation and Its Implication on Employee’s Performance - Elvie Maria; Anoesyirwan Moeins (International Journal of Supply Chain Management, 2020)
Abstract— The purpose of this study was to know and analyze the Influence of supply chain management toward work motivation and it’s implication to employee performance. The method used in this research were descriptive survey method and explanatory survey. The population in this study amounted to 254 employees of BPNM (Christian Education Agency in Medan), with a sample size of 205 respondents. Analysis technique and hypothesis testing using Structural Equation Modeling (SEM) with LISREL 8.70 program. The result of research found that supply chain had positive and significant influence toward work motivation. Then also toward employee performance both partially and simultaneously supply chain management and work motivation had positive influence and significant. While, contribution percentage of supply chain, toward work motivation is 72% and contribution percentage of work motivation simultaneous toward employee performance is 85%. The implication on this research is that the employee performance especially on the quantity   will be able to be improved if BPNM able to increase work motivation especially to the needs’ motivation, work motivation will increase if BPNM is able to increase the leadership, especially in attitude dimension towards human, and increase the SCM especially to the internal integration, and supported by the improvement of interpersonal communication, mainly in social relationship. Furthermore, work motivation only have role for supply chain toward employee performance, while for SCM variable, work motivation don’t have role to escalate  employee performance, so in this model work motivation only as partial mediating.